2014
DOI: 10.1038/ki.2013.290
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial transduction of lentivirus-shRNA-VEGF-A in arteriovenous fistula reduces venous stenosis formation

Abstract: Venous neointimal hyperplasia (VNH) causes hemodialysis vascular access failure. Here we tested whether VNH formation occurs in part due to local vessel hypoxia caused by surgical trauma to the vasa vasorum of the outflow vein at the time of arteriovenous fistula placement. Selective targeting of the adventitia of the outflow vein at the time of fistula creation was performed using a lentivirus-delivered small hairpin RNA that inhibits VEGF-A expression. This resulted in significant increase in mean lumen vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(138 citation statements)
references
References 41 publications
6
132
0
Order By: Relevance
“…These can be divided into their mechanisms of action based on inflammation, oxidative stress, fibrosis, and endothelial dysfunction (several potential targets are discussed in preceding sections and below) (Figure 3). Recently, experimental studies have demonstrated that anti-VEGF-A therapy using bevacizumab treatment before the placement of experimental AVF is protective for formation of venous stenosis (Figure 4) (73). In a small group of patients who received intravitreal treatment of bevacizumab for macular degeneration before the placement of a hemodialysis vascular access, the Misra laboratory showed that the median patency was improved more than two-fold compared with control group (paper under review).…”
Section: Potential Future Molecular Targets That May Translate Into Tmentioning
confidence: 99%
See 1 more Smart Citation
“…These can be divided into their mechanisms of action based on inflammation, oxidative stress, fibrosis, and endothelial dysfunction (several potential targets are discussed in preceding sections and below) (Figure 3). Recently, experimental studies have demonstrated that anti-VEGF-A therapy using bevacizumab treatment before the placement of experimental AVF is protective for formation of venous stenosis (Figure 4) (73). In a small group of patients who received intravitreal treatment of bevacizumab for macular degeneration before the placement of a hemodialysis vascular access, the Misra laboratory showed that the median patency was improved more than two-fold compared with control group (paper under review).…”
Section: Potential Future Molecular Targets That May Translate Into Tmentioning
confidence: 99%
“…In addition, in AVGs there is an active macrophage cell layer lining on the polytetrafluoroethylene graft itself (28,30). Several publications have demonstrated that neointimal hyperplasia is related to endothelial cell activation, activation, and infiltration of circulating inflammatory cells, along with production of chemokines and growth factors that regulate migration of smooth muscle cells and myofibroblasts into the intimal layer of the vessel (23,31). Moreover, several perivascularly delivered antiproliferative therapies have been evaluated in AVG (32,33), but none of these studies have advanced past early phases in clinical trials.…”
Section: Neointimal Hyperplasia In Avf Maturation Failure and Avg Dysmentioning
confidence: 99%
“…These include vein configuration (22), hemodynamics stress (39), inflammation (20), and preexisting diseases like diabetes (40) and kidney failure (26). The above conditions induce de novo accumulation of growth factors such as VEGF (48), plateletderived growth factor (41), fibroblast growth factor (42), and transforming growth factor-␤ (18) and their receptor tyrosine kinases (RTKs) in the outflow vein, which ultimately increase the proliferation, migration, and survival of neointimal cells and the subsequent thickening of the vessel wall. Recently, vascular expression of stem cell factor (SCF) and its receptor c-Kit have also been implicated in A-V fistula NIH (8).…”
mentioning
confidence: 99%
“…To assess the efficacy of glycemic changes upon the invasiveness of fibroblasts and myofibroblasts, the expression of the constitutive matrix regulatory and signaling moiety of Mmp-2 was silenced with lentivirus (LV)-mediated shRNA transduction [4,17]. Briefly, AKR-2B cells were seeded into 10-cm dishes and grown to about 50-60% of confluency.…”
Section: Methodsmentioning
confidence: 99%
“…AVFs have been used for more than 50 years and are prone to venous stenosis formation [2]. Although the exact mechanism for venous stenosis is not yet clear, several major factors have been hypothesized including hypoxia, shear stress, oxidative stress and inflammation [3,4]. As a consequence, these factors lead to an accumulation of macrophages, fibroblasts and smooth-muscle cells in the vessel wall, that lead to stenosis formation [5].…”
Section: Introductionmentioning
confidence: 99%